Spatial Modeling of the Impact of Human and Public Capital on Employment Convergence between Regions in Morocco: Time Period from 2010 to 2023. - Marmad Toufik; Ritahi Oussama (ECONOMICS)
This article explores spatial convergence in Morocco to assess whether the benefits of development are equitably distributed across regions, recognizing that growth in one region can influence its neighbors. It examines employment convergence, focusing on the role of human and public capital within a framework of geographical interdependencies. The goal is to test whether these forms of capital contribute to reducing employment disparities between regions. Combining a comprehensive literature review on economic convergence with an empirical analysis specific to Morocco, the study reveals that public capital, especially capital expenditures and the presence of public institutions, plays a critical role in driving convergence. Similarly, human capital, measured by school enrollment rates, contributes to reducing employment inequalities and fostering balanced regional development. The research highlights that investments in both human and public capital, particularly in infrastructure and education, are essential for narrowing regional employment gaps. The SDM model, which captures both endogenous and exogenous interactions, is found to be the most reliable for understanding these dynamics. The study further estimates the economic catch-up speed between regions at 5.5%, indicating slow progress. At this rate, less-developed regions are moving toward the employment levels of more prosperous regions at a yearly pace of 5.5%. This gradual advancement reflects deep-rooted structural and socio-economic challenges, requiring sustained efforts over time. The projected half-life of over 16 years suggests that it will take more than 16 years to halve employment disparities, underscoring the long-term commitment required to achieve significant convergence.